2004
DOI: 10.1093/annonc/mdh017
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of viable circulating endothelial cells are an indicator of progressive disease in cancer patients

Abstract: In progressive cancer patients, the amount of CECs is increased. These CECs are viable and may contribute to vessel formation. The number of CECs is influenced by anticancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
214
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(236 citation statements)
references
References 41 publications
12
214
1
3
Order By: Relevance
“…In concordance to literature our comparison of controls and newly diagnosed breast cancer patients showed increased numbers of CEC in the cancer patients with both methods (Mancuso et al, 2001;Beerepoot et al, 2004). In real-time PCR the difference was more pronounced as in the flow cytometric detection.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In concordance to literature our comparison of controls and newly diagnosed breast cancer patients showed increased numbers of CEC in the cancer patients with both methods (Mancuso et al, 2001;Beerepoot et al, 2004). In real-time PCR the difference was more pronounced as in the flow cytometric detection.…”
Section: Discussionsupporting
confidence: 90%
“…Unfortunately, clinical markers to assess neoangiogenesis in patients or the response to antiangiogenic treatment are still scanty. Circulating endothelial cell numbers in peripheral blood seem to be a relevant marker of neoangiogenesis since CEC are elevated in cancer patients and the amounts of CEC correlates with progressive disease (Mancuso et al, 2001;Beerepoot et al, 2004). The amounts of CEC in peripheral blood can be measured by flow cytometry, but this requires fresh blood samples and a complex four-colour analysis with the acquisition of many events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Kaplan et al (2005) reported that bone marrow-derived HPCs express VEGFR1 home to tumour-specific premetastatic sites, and form cellular clusters that provide a permissive niche for incoming tumour cells before the arrival of tumour cells. Another possible source may be mature vessel-derived endothelial cells, which might be the largest source of VEGFR1-expressing circulating endothelial cells (CECs) (Mancuso et al, 2001;Beerepoot et al, 2004). Contrary to our expectation, there was no significant difference in the number of VEGFR1-expressing cells of CD133 þ /À CD31 þ Figure 1 VEGFR1 mRNA expression in peripheral blood from gastric cancer cases.…”
Section: Discussionmentioning
confidence: 81%
“…Since several new antitumor drugs target tumor angiogenesis or tumor vasculature, CEC counts are a potential surrogate marker for assessing drug efficiency and therefore hold promise to avoid over-or undertreatment of individual patients. In addition, reductions in CEC concentrations may reflect tumor growth and thereby serve as a parameter to reveal disease progression at an early stage (9).…”
mentioning
confidence: 99%